2011
DOI: 10.1007/s12548-011-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orthodontic reconstruction on brain activity in a patient with masticatory dysfunction

Abstract: Brain functional magnetic resonance imaging (fMRI) was used to evaluate the effect of malocclusion therapy on the brain activity of a patient with malocclusion. A 29-year-old female patient had difficulty opening the mouth with occasional pain in the left temporomandibular joint (TMJ) and a maximum opening of only 29 mm. The treatment objectives included repositioning the displaced mandible and establishing occlusal support. Orthodontic treatment took 14 months. Treatment results were satisfactory in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A steep anterior occlusal plane [54] involves an avoidance pattern [55] due to the avoidance of too strong front tooth contacts in the transversal, retrusive or protrusive direction [56], leading to a load of the structures of the temporomandibular joint [57,58] and to a constant hypertonicity of the muscles. This additional load involves a neurological reaction of the body leading to even more muscle activity [26,1,39]. Moreover, in the majority of cases a steep posterior occlusal plane provides a significantly higher chance for the occurrence of laterotrusive and mediotrusive or even retrusive posterior interferences [59], again making an avoidance-which in turn will lead to more compensatory necessity of the system to increase the activity of the neurological system, enhanced muscle activity [60] and condylar displacement.…”
Section: International Journal Of Dentistry and Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A steep anterior occlusal plane [54] involves an avoidance pattern [55] due to the avoidance of too strong front tooth contacts in the transversal, retrusive or protrusive direction [56], leading to a load of the structures of the temporomandibular joint [57,58] and to a constant hypertonicity of the muscles. This additional load involves a neurological reaction of the body leading to even more muscle activity [26,1,39]. Moreover, in the majority of cases a steep posterior occlusal plane provides a significantly higher chance for the occurrence of laterotrusive and mediotrusive or even retrusive posterior interferences [59], again making an avoidance-which in turn will lead to more compensatory necessity of the system to increase the activity of the neurological system, enhanced muscle activity [60] and condylar displacement.…”
Section: International Journal Of Dentistry and Oral Healthmentioning
confidence: 99%
“…Two subtypes of Dist occlusion are Class II, Division 1 with protruded upper anterior teeth and Class II, Division 2: here the Based on the concepts of occlusion by Professors Slavicek and Sato [26], we have taken up the case study of several patients in this thesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that many patients with malocclusion complaints experience comorbid mental stress and somatic symptoms [ 1 – 3 ]. Additional studies have suggested that malocclusion may be linked to higher brain function [ 4 6 ]. An experimental animal study induced occlusal disharmony in rats by attaching metal wires to the biting surfaces of both maxillary molar teeth with resin cement to artificially raise the vertical dimension of occlusion (VDO).…”
Section: Introductionmentioning
confidence: 99%
“…Current methods used to measure human brain function in medical and clinic research include positron emission tomography (PET), magnetoencephalography (MEG), fMRI, and near-infrared spectroscopy (NIRS). These neuroimaging techniques have also been used in the field of dentistry to study the effects of various oral functions on the brain [ 4 , 5 , 11 20 ]. However, the results of this research have yet to be translated into clinical dental applications, since the aforementioned systems are often expensive and difficult to operate, while fMRI and MEG require the patient’s head to be secured and the patient’s posture to be limited.…”
Section: Introductionmentioning
confidence: 99%